Recent Trends in Fluorescent Organic Materials for Latent Fingerprint Imaging - Lian, Jie; Meng, Fanda; Wang, Wei; Zhang, Zhitao (Frontiers in Chemistry, 2020)
Fingerprints are an important kind of material evidence with the key function in personal identification, which are unique and life-long to everyone. Latent (invisible) fingerprints are common at the crime scene, needing to be visualized with proper methods in order to identify sources of the fingerprints in routine forensic practice. Fluorescent imaging of latent fingerprints has the advantage of high contrast, sensitivity, selectivity and less dependency on instruments. Taking the environment and users’ safety into consideration, organic materials for fluorescent imaging of latent fingerprints are reviewed mainly in recent five years. New strategies of fingerprint reagents and improved performances established for fingerprint development based on fluorescent organic materials are discussed in the view of forensic practice. In addition, we briefly highlight current challenges of recent fluorescent imaging works based on organic materials for the latent fingerprints development in forensic practice.